A Proposed Integrated Human Recognition for Security Reassurance - Fatma Susilawati, Mohamad; Zahraddeen, Sufyanu; Ahmad Salihu, Ben-Musa (Science Publications, 2015)
A lot of systems require reliable and thorough authentication to ratify individual’s claimed identity, especially in national and international security and defense. Unibiometric system suffers inherent weaknesses that are unavoidable in the system. Such inadequacies may directly or indirectly lead to an unacceptable error. For this reason, researchers pay great attention to the more advanced biometrics (referred to as multimodal biometrics). A multimodal biometric system involves at least two unimodal traits in a sole identification. This alleviates some of the drawbacks and improves recognition accuracy despite number of population considered. This research proclaims a new technique of integration for human recognition improvement using four physiological characteristics: Face, iris, palmprint and thumbprint. In addition, two fusion strategies namely, score-level and decision-level are presented using robust algorithms. The multimodal biometric systems possessed relative merits or pluses over its counterpart monomodal biometrics. The higher biometric modalities are integrated the more system is secured, hence better security assurance. Therefore, successfully conducting our research can derive supreme benefit over conventional multimodal biometrics. The integration results to outstanding gap coverage for security reassurance.